Research on assembly stress and deformation of thin-walled composite material power cabin fairings - Dong Yushuang; Li Bianhong; Zhang Houjiang; Gao Hanjun (Reviews on Advanced Materials Science)
As a critical component of a helicopter, the issue of assembly continuity deviation between the fairing and adjacent components during the assembly process can significantly impact flight stability and safety. The traditional fairing assembly process typically emphasizes basic alignment and fixation, often neglecting an analysis of the factors that influence its shape and performance characteristics. This study simulates the fairing assembly model under various working conditions to investigate stress distribution and deformation characteristics. The goal is to identify the primary factors that lead to changes in the shape and performance of the fairing and to summarize the overall stiffness distribution of the fairing. To ensure the accuracy of the constructed finite-element model of the fairing, experiments were initially designed to determine the intrinsic parameters of the fairing composites. This process aimed to obtain key data, such as the elastic modulus and Poisson’s ratio. Following this, a mechanical plate loading test simulating equivalent cutting of the fairing was conducted, and a corresponding simulation model was developed using ABAQUS software. By comparing the results from the tests and simulations of the mechanical plate, the feasibility of applying the determined intrinsic parameters to the fairing finite-element model was effectively validated. Subsequently, a three-dimensional model of the fairing was created in CATIA software and imported into ABAQUS for analytical modeling, allowing for the simulation and analysis of the fairing’s force conditions under various constraints. The results indicate that the overall stiffness of the fairing is influenced by fixed-boundary constraints and external forces. Additionally, the stress experienced by the fairing is negatively correlated with the width of the fixed-boundary constraints; as the width increases, the stress decreases continuously. This decrease is more pronounced in the initial stages and gradually slows down in later stages. Specifically, the stress decreases by as much as 79.25% within the constraint width range of 10–20 mm, while the reduction slows to 46.2% in the 60–80 mm range. The shape and performance of the fairing are influenced by various factors, with displacement load and clamping distance being the primary determinants. The effects of these two factors on fairing stress vary dynamically with changing working conditions. Notably, under different clamping distances, a significant linear relationship exists between displacement load and deformation. For instance, at a clamping distance of 200 mm, the difference between adjacent deformations stabilizes at 0.516 mm, with a relative deviation strictly controlled within ±3%. When the clamping distances are increased to 600 and 1,000 mm, the dispersion of the deformation increments relative to their mean values remains low, with the ratio of the standard deviation to the mean value being 2.5 and 2%, respectively.